An empirical investigation of the performance of Japanese mutual funds: Skill or luck? - Keith Pilbeam; Hamish Preston (International Journal of Financial Studies, 2019)
This paper assesses the performance of 355 actively managed Japanese Equity Mutual Funds between April 2011 and April 2016. The equal weight portfolio and Jensen's alpha measures of active management provide strong evidence that Japanese Mutual Funds fail to outperform the benchmark four-factor capital asset pricing model. When it comes to market timing, the Treynor and Mazuy measure shows that 33 funds have significant positive market timing ability which is largely offset by 31 funds with significant negative timing ability. To ensure the statistical inference is robust to the non-normality found in 33 funds we employ Fama and French's cross-sectional bootstrap. The results show that a large proportion of funds fail to outperform a hypothetical world with no skill. On the persistence of skill we find that there is stronger persistence for poor performing funds than for strong performing funds.
Keywords: C15; G11; 330; mutual fund performance; bootstrap; Jensen's alpha; Fama and French model